What Motivates Reasoning? A Theory of Goal‐Dependent Political Evaluation. Issue 1 (20th October 2020) - Groenendyk, Eric; Krupnikov, Yanna
Abstract: Rather than exhibiting bias or open‐minded reasoning at baseline, we argue that information processing is motivated by whatever goals a context makes salient. Thus, if politics feels like debate, people will be motivated to argue for their side. If politics feels like deliberation, they will be motivated to seek consensus through open‐minded processing. Results from three experiments demonstrate: (1) Politics evokes thoughts similar to conflictual contexts and dissimilar from deliberative contexts. (2) Consequently, information labeled "political" primes the motivation to counterargue, leading to opinion polarization. Absent such labeling, no such motivation is evident, explaining why bias is common but not inherent to politics. (3) Despite this capacity for bias, people can be motivated to actively process and accept counterattitudinal information by simply making the value of open‐mindedness salient. This suggests open‐minded discourse is possible even absent motivation to evaluate information accurately. We conclude by discussing the implications of our research for political discourse.